ANALISIS TATA KELOLA BANK SAMPAH DI KABUPATEN BENGKALIS - Della Anna; Nurmasari Nurmasari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2017)
This research was conducted to see the waste management carried out by the garbage bank in Bengkalis Regency. The type of data used in this study includes primary data and secondary data. Data collection techniques used were observation, questionnaires, documentation and interviews. The data analysis technique used by the writer is descriptive qualitative in the form of tables and depictions through the results of interviews in the field by looking at respondents' answers to the management of waste banks in Bengkulu district in the form of collected data analyzed by describing existing problems and providing Interference with relevant results is then concluded. From the research it can be concluded that the results obtained are still that the waste management by the garbage banks of Bengkulu district is quite implemented.